Torsional Wave Propagation in the Finitely Pre-Stretched Hollow Bi-Material Compound Circular Cylinder - Akbarov, Surkay D.; Kepceler, Tamer; Egilmez, M. Mert; Dikmen, Ferhat (TECH SCIENCE PRESS, 2011)
This paper studies the torsional wave dispersion in the hollow bi-material compounded cylinder with finite initial strains. The investigations are carried out within the scope of the piecewise homogeneous body model with the use of the three-dimensional linearized theory of elastic waves in initially stressed bodies. The mechanical relations of the materials of the cylinders are described through the harmonic potential. The numerical results on the influence of the initial stretching or compression of the cylinders along the torsional wave propagation direction are presented and discussed
Keywords: finite initial strains; wave dispersion control; hollow bi-material compound cylinder; high elastic material; torsional wave; AXISYMMETRICAL LONGITUDINAL-WAVES; DISPERSION-RELATIONS; Computer Science; Materials Science